The Paradigm of Water Justice in Water Resources Law and the Role of Family in the Sustainable Development Goals Framework: A Study in Malang Raya - Jundiani, Jundiani; Fadli, Moh; Dwi Qurbani, Indah; Kurniaty, Rika; Zuhriah, Erfaniah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The paradigm of water justice in water resources law is crucial in realizing fair and sustainable access for the community. This study highlights the problems of inequality in water distribution due to privatization and the implementation of policies that have not fully supported vulnerable communities. This study focuses on the regulation of water resources law in Indonesia, especially Law No. 17 of 2019, and the contribution of families in supporting the principle of water justice within the framework of the Sustainable Development Goals (SDGs). The main questions answered in this study include how current regulations regulate water distribution and access, how effective they are in implementation in Malang Raya, and the role of families in supporting sustainable water management. This type of research is empirical juridical with a sociological juridical approach and an empirical legal approach. Data were obtained through legal document studies, interviews with stakeholders, and direct observation of water consumption and management patterns in local communities. The results show that although national regulations have established water as a public right, its implementation still faces challenges, including an imbalance of access between urban and rural areas, industrial dominance in the use of water resources, and weak community participation in policy processes. The study also found that families have a strategic role to play in educating household members about water conservation and driving more inclusive local policies. This study recommends increasing the role of families in water management policies through community-based environmental education and awareness programs, as well as strengthening regulations to ensure a more equitable distribution of water. Thus, the implementation of the principle of water justice in water resources law can be more effective in supporting the achievement of SDG 6.